Upaya Pengelolaan Diabetes Melitus Tipe 2 Dengan Pendekatan Pelayanan Dokter Keluarga - Noviana Zara; Muhammad Alief Hawari (STIKes Ibnu Sina Ajibarang, 2023)
A 52-year-old female patient came to the Muara Batu Health Center with complaints of tingling hands and feet which were getting worse every day, especially in the last 5 days. Initially, the feeling of tingling was only felt in the two feet, but in the last 3 days, the feeling of tingling had also been felt in both hands. Another complaint felt by the patient is that the patient often urinates at night. Based on the results of the anamnesis, the patient has a history of type 2 diabetes mellitus since ± 3 years ago. Based on the results of anamnesis related to family history, it is known that the patient's father also has a history of type 2 diabetes mellitus. The patient has often come and seek treatment at the Puskesmas. On physical examination, BP 130/90 mmHg, RR 19 x/minute, HR 81 x/minute, BMI 20.44 kg/m2. Primary data were obtained through anamnesis and physical examination by conducting home visits, filling out family folders, and filling out patient files. The assessment was carried out based on the initial holistic diagnosis, process and end of the visit both quantitatively and qualitatively. The interventions were in the form of promotive, preventive, curative, rehabilitative and psychosocial efforts.